KONSER SALAM DUA JARI SEBAGAI SEBUAH KAMPANYE POLITIK: ANALISIS SIMULAKRA DAN ANALISIS WACANA KRITIS - muhammad rifky rahman dwi putra; Priyatno Harsasto .; puji astuti . (Journal of Politic and Government Studies, 2017)
ABSTRACTKonser Salam Dua Jari are supported by hundreds of musicians and creative economist toSupport Jokowi-Jk as a presidential-vice presidential candidate, managed to emerge as one of thephenomenon in 2014 due to the presidential election and won the attention over various layers ofcommunity in Indonesia. The problem that arises is how people, especially swing voters,addressing the concert? Is Konser Salam Dua Jari able to provide its own sign or just ends upbeing a regular music concert? Is Konser Salam Dua Jari can explain to what extent the bargainingposition of music in the 2014 presidential election?The aim of research is to explain the position of Konser Salam Dua Jari in the eyes offloating voters and explain the position of music in 2014 presidential election. Where an effort toaddress concerns and objectives of research will be done by using the theory of Simulacra thatfocuses on practical sign to build a simulation.This research is a descriptive research which uses a qualitative approach. This researchusing critical discourse analysis approach by Pecheux. The analytical method used is theframework discourse which Sara Mills proposed by observing the position of the subject-objectposition and their reader-writer position.The results showed that Konser Salam Dua Jari able to give a sign of the magnitude ofpublic support to Jokowi. This means also that Konser Salam Dua Jari is not only a regular musicconcert, it is also supported by news in various online media. Music can also be said to be able toshow its strength as a medium of political campaigns.Key Words: Konser Salam Dua Jari, Political Campaign, Simulation; Counterfeit